Examining price convergence behaviour between Peninsular Malaysia and Sabah & Sarawak: evidence for market integration - Mhd. Ruslan, Siti Marsila; Mat Ghani, Gairuzazmi; Khalid, Haniza (2016)
The purpose of this study is to assess the degree of markets integration within Malaysia by examining price convergence across East and West Malaysia markets. Disaggregate monthly price data (consumer price index) for various categories of goods or services in Peninsular Malaysia, Sabah and Sarawak were utilized from year 2004 to 2015 using ADF unit root test and half-life estimation. Our empirical findings show that there is a price convergence for majority of price commodity groups in Malaysia. The implication of price convergence in Malaysia gives the evidence of market integration among Peninsular Malaysia, Sabah and Sarawak. On the other hand, most of tradable goods prices adjust more rapidly than non-tradable goods when looking at its half-life period.